Students' Perception of Digital Technology Supporting English Learning in Globalization Era - Vera Tri Anmary; Yulia Nugrahini (Politeknik Kampar, 2024)
Students use digital technology to facilitate their learning, particularly when learning English. This is driven by the COVID-19 pandemic, which necessitates online learning. Based on this background, the purpose of this study is to find out how students' perceptions of digital technology support English language learning in the era of globalization and what digital technology students use in learning English. This research method uses qualitative research with descriptive qualitative analysis techniques. The subjects of this study were 6th semester students at Bhinneka PGRI University with a total of 27 students. The data collection techniques used were open questionnaires and closed questionnaires. The results of the research that have been obtained by researchers are known that almost all students feel helped by the existence of digital technology around them in learning English. This is because digital technology is considered more effective and time efficient to be used anywhere and anytime. One digital tool that students use to learn English is social media. They believe that, in the age of globalization, social media can help them improve their English language proficiency. Students are also affected by globalization because English is the language of communication on a worldwide scale.